Rantai Pasok Komoditas Cabai pada Pilot Project Close Loop Agribisnis di Kabupaten Garut - Fitri Awaliyah; Wahid Erawan (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2023)
Chili is a horticulture sub-sector commodity whose price often fluctuates. Chili price fluctuations that occur are generally caused by an imbalance in the amount of supply and demand. The aim of this research is to identify and examine the chili supply chain management that occurs in the Close Loop Agribusiness Pilot Project in Garut Regency. The research method used is a qualitative research method. The research location was chosen purposively in Cikajang District, Garut Regency, namely the first location where the close loop agribusiness pilot project was implemented. The data collection method was carried out by means of in-depth interviews with the agribusiness institutions involved, namely the Eptilu Cooperative and partner farmers using a structured questionnaire instrument. The analytical method used is descriptive analysis using FSCN (Food Supply Chain Networking) process analysis. The research results show that the chili supply chain structure in the closed loop agribusiness program consists of several actors who are integrated with each other to process the flow of goods, information and money. The actors involved include agricultural production facilities companies as providers of seeds, fertilizer and agricultural medicines, banks as capital distributors, partner farmers as actors in the cultivation process, the Eptilu Cooperative as the marketing and processing process for chilies, and customer companies that purchase chili supplies from the Eptilu Cooperative , as well as marketing chili to consumers through traditional markets, supermarkets, hotels, restaurants, catering or marketing directly. This supply chain is supported by productive farmer partners, the Eptilu Cooperative and agricultural production facilities companies that are proactive and responsive to farmers' needs. Supported by updating digital technology regarding effective cultivation processes based on Good Agricultural Practice.